Optimising Down payment Management in Project-Based Sales : A Case Study: Enhancing Financial Communication at Wärtsilä through Continuous Improvement - Ojala, Tuomas (My University, 2025)
In project-based delivery, managing payment processes is a key element of cash flow predictability and risk management, especially in industries that focus on long lead times and customised solutions. In the context of Wärtsilä's marine business, timely down payments are particularly critical to ensure the financial stability of projects, as they directly affect the company's liquidity, the timing of procurement and the coordination of project financing. The smoothness of payment processes is therefore essential not only for financial management but also for the functioning of the organisation as a whole. The aim of this study is to improve the efficiency of the payment process by analysing the impact of organisational structures, internal communication and process management on the handling of down payments at the early stages of projects. The study will examine how collaboration between finance and sales influences the way and timing in which payment terms and invoicing are prepared for customer projects. The aim is to identify bottlenecks in the processes and suggest improvements to enable a more proactive and coordinated approach to payment management. The study was conducted as a case study in Wärtsilä's marine business area. The empirical data consists of semi-structured interviews with stakeholders from sales, finance and project creation. The interview material was supplemented with perspectives based on organisational theory, process management and Lean thinking in order to examine payment processes and their efficiency through both practical and theoretical understanding. The theoretical framework is based on the impact of organisational structures on business processes, particularly from the perspective of financial workflows. The study examines how different organisational models, such as functional, divisional, matrix and process orientation, affect the flow of information and the allocation of responsibilities. It also uses Lean principles to streamline processes and identifies the mechanisms that support the management of a project environment. The empirical results highlight three key challenges: 1) late involvement of financial management in the early stages of projects, 2) poor integration of systems and 3) workflows that rely on manual steps. As a result, the payment process is slowed down, making invoicing and project creation timing more difficult. The study suggests clarifying roles and defining handover points between departments to streamline the process.

Projektipohjaisissa toimituksissa maksuprosessien hallinta on keskeinen osa kassavirran ennustettavuutta ja riskienhallintaa, erityisesti pitkiin toimitusaikoihin ja asiakaskohtaisesti räätälöityihin ratkaisuihin keskittyvillä toimialoilla. Wärtsilän meriliiketoiminnan kontekstissa oikea-aikaiset ennakkomaksut ovat erityisen kriittisiä projektien taloudellisen vakauden turvaamiseksi, sillä ne vaikuttavat suoraan yhtiön likviditeettiin, hankintojen ajoitukseen ja projektirahoituksen koordinointiin. Maksuprosessien sujuvuus on siten paitsi taloushallinnon myös koko organisaation toiminnan kannalta olennainen tekijä. Tämän tutkimuksen tavoitteena on parantaa maksuprosessin tehokkuutta analysoimalla organisaatiorakenteiden, sisäisen viestinnän ja prosessinhallinnan vaikutuksia ennakkomaksujen käsittelyyn projektien alkuvaiheessa. Tutkimuksessa selvitetään, miten taloushallinnon ja myynnin välinen yhteistyö vaikuttaa siihen, millä tavoin ja aikataululla maksuehdot, laskutus ja vakuudet saadaan valmisteltua asiakasprojektien yhteydessä. Tarkoituksena on tunnistaa prosessien pullonkaulat ja esittää kehitysehdotuksia, jotka mahdollistavat ennakoivamman ja koordinoidumman lähestymistavan maksujen hallintaan. Tutkimus toteutettiin tapaustutkimuksena Wärtsilän meriliiketoiminta-alueella. Empiirinen aineisto koostuu puolistrukturoiduista haastatteluista, jotka toteutettiin myynnin, taloushallinnon ja projektin luonnin asiantuntijoiden kanssa. Haastatteluaineistoa täydennettiin organisaatioteoriaan, prosessijohtamiseen ja Lean-ajatteluun perustuvilla näkökulmilla, jotta maksuprosesseja ja niiden tehokkuutta voitiin tarkastella sekä käytännön että teoreettisen ymmärryksen kautta. Teoreettinen viitekehys pohjautuu organisaatiorakenteiden vaikutuksiin liiketoimintaprosesseissa, erityisesti taloudellisten työnkulkujen näkökulmasta. Tutkimuksessa tarkastellaan, miten eri organisaatiomallit, kuten toiminnallinen, divisioonapohjainen, matriisi- ja prosessiorientaatio, vaikuttavat tiedon kulkuun ja vastuunjakoon rahoitusprosessien osalta. Lisäksi hyödynnetään Lean-periaatteita prosessien virtaviivaistamiseen ja tunnistetaan, millaiset mekanismit tukevat ennakkomaksujen hallintaa projektitoimintaympäristössä. Empiiriset tulokset nostavat esiin kolme keskeistä haastetta: 1) taloushallinnon myöhäinen osallistuminen projektien alkuvaiheessa, 2) järjestelmien heikko integraatio ja 3) manuaalisiin vaiheisiin nojaavat työnkulut. Näiden seurauksena maksuprosessi hidastuu, mikä vaikeuttaa laskutusta, vakuushallintaa ja projektin luonnin ajoitusta. Tutkimus ehdottaa roolien selkeyttämistä ja osastojen välisten luovutuspisteiden määrittelyä prosessin jäntevöittämiseksi.
Keywords: down payments, financial communication, project-based sales, process development, ennakkomaksut, taloudellinen viestintä, projektipohjainen myynti, prosessien parantaminen